CompEx asthma: a novel composite exacerbation endpoint - Da Silva, Carla A. (Henry Stewart Talks, 2019)
A composite/surrogate endpoint for asthma severe exacerbations (CompEx), Predicting treatment efficacy on asthma severe exacerbations with CompEx, Overview of clinical trials used to develop CompEx asthma, Methodology to build diary events, Definition of a CompEx Asthma event, CompEx asthma algorithms, CompEx asthma performance vs. severe exacerbations, Acceleration of clinical development through CompEx asthma